Impact of wine-grape continuous cropping on soil enzyme activity and the composition and function of the soil microbial community in arid areas - Song, Rui; Zhu, Wen Zong; Li, Hua; Wang, Hua (Frontiers in Microbiology, 2024)
Continuous cropping affected the stability of soil enzyme activity and the structural characteristics of microbial community. Wine grapes are often planted continuously.However, understanding its impacts on microbial and biochemical characteristics of the soil remains limited. To investigate the succession trends in the microbial communities of vineyards under continuous cropping, metagenomic sequencing was conducted on the rhizosphere soils from one uncultivated wasteland and four vineyards with varying durations of continuous cropping.The predominant microbial were bacteria (98.39%), followed by archaea (1.15%) and eukaryotes (0.45%). Continuous cropping caused a significant increase in the relative abundance of Rhizobiales and Micrococcales but a marked decrease in Solirubrobacterales. At the genus level, 75, 88, 65, 132, and 128 microbial genera were unique to uncultivated wasteland, 5, 10, 15, and 20 years of continuous cropping, respectively. The relative abundance of genes with signal transduction function was the highest. The activity of all enzymes measured in this study peaked at 5 years of continuous cropping, and then decreased with 10 to 15 year of continuous cropping, but increased at 20 years again. In addition, soil enzyme activity, especially of alkaline phosphatase was significantly correlated with the diversity of the dominant microorganisms at the genus level.Moreover, the coupled enzyme activities had a greater impact on the diversity of the microbial community than that of individual enzymes. Overall, Our findings reveal the composition and function of the soil microbial communities and enzymes activity in response to changes in cropping years, which has important implications for overcoming continuous cropping obstacles and optimizing land use.